The Boltzmann Constant for the Definition and Realization of the Kelvin. Issue 5 (27th December 2018) - Fischer, Joachim
Abstract: In November 2018, the four base units, kilogram, ampere, kelvin, and mole, of the International System of Units (SI) are redefined in terms of fundamental physical constants. The redefinition comes into force on World Metrology Day, 20 May 2019. The kelvin, the base unit of thermodynamic temperature, from then is to be founded on a fixed numerical value of the Boltzmann constant. Herein, the change in the definition of the kelvin and the consequences for practical temperature measurement are explained. The primary thermometry methods applied to determine the numerical value of the Boltzmann constant for the redefinition are reviewed. The prospects for the future application of these methods are outlined. Abstract : In the revised International System of units, the unit of temperature T, the kelvin is based on a fixed numerical value of the Boltzmann constant k . Thus, temperature measurement is, in principle, a comparison to the standard amount of microscopic thermal energy, kT, specified by the Boltzmann constant. The photograph shows a detector operating accordingly to sense thermal radiation.